Potential Politics Cash in a Moving the Growth Economic Development in a Shadow Exchange Commercial Regional Level Non Equivalent with Iraq - Jalil Abdulhasan, Abdulhussein; Bdaiwi Khudhair, Layla; Asfore Lafta, Abaas (International Journal of Psychosocial Rehabilitation, 2020)
That Policies Cash Which Followed Countries Good Regional level Iraq desire Of which in Expansion Commercial Reduction Values Currencies Effect On Activity Economic development Production, In a manner Clear So The This search Spins About this is the problem. He tries to Signal to me Possibilities Which owns the politics Cash To move Life Economic development in a Iraq in a Shadow. This Exchange Commercial Non Equivalent With That Countries. He arrived to me Results Of which that country’s Good Regional level, Especially Turkey And Iran Continue to Reduction Values Their currencies Wan. Their trade in a expansion continued with Iraq. There A struggle Commercially Between them acquisition of Period Larger in a market Iraq And transgression This Conflict border Confidentiality Commercial to me The statements Public And here most of the Bank Central And the Government Iraq must take short-, medium-And long Term To protect Production the local And increase it by providing The environment Occasion for him Pictures From Goods Foreign The competition And steering Life Economic development Iraq Toward Production allowance Import .